FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM SYARIAH (Study pada Saham yang terdaftar di JII 2005-2010) - Eko Supriyanto, 08.05.52.0103; Suwarti, Titiek (Students Journal of Accounting and Banking, 2012)
This study aims to provide empirical evidence, Factors - Factors affecting retrun Islamic stocks (study on stocks listed in JII (Jakarta Islamic index).Objects in this study is a company registered in the JII (Jakarta Islamix Index) in 2005 until 2010. The samples in this study were nine companies. The method used in the sampling is purposive sampling method. Statistical analysis tool used is multiple regression with a significance level.The results of the analysis said that earnings per share and return on investment have a significant and positive then hopotesis acceptable. While the debt to equity ratio and significant and positive effect of inflation, price-book value and the exchange rate is not significant then the hypothesis is rejected, firm size is not significant then the hypothesis is accepted.Keywords: Earnings per share, Retrun on investment, debt to equity ratio, price-book value, the size of the company, of inflation, exchange rates and stock returns sharia.